Acute murine cytomegalovirus infection boosts cell-type specific response and lipid metabolism changes in the liver of infant mice - Gao, Juanzi; Wang, Anmin; Bu, Xiangyi; Jia, Weidong (Frontiers in Immunology, 2023)
Introduction Human cytomegalovirus (HCMV) infection in infants can lead to severe diseases, including neonatal hepatitis. The single-cell dimensional changes in immune cells after the initial CMV infection remain elusive, as do the effects of CMV infection on hepatic lipid metabolism. Methods We employed single-cell RNA-sequencing to investigate the changes in liver cell types and immune responses in infant mice following murine CMV (MCMV) infection. Additionally, we examined alterations in protein expression profiles related to lipid metabolism in hepatocytes and the role of the key transcription factor PPAR-γ in hepatocytes during CMV infection. Results Our study revealed that MCMV infects most liver cell types in infant mice, leading to an increase in the proportion of proliferating CD8 effector T cells and a subset of Nos2+ monocytes, potentially playing an essential role in early anti-viral responses. Furthermore, MCMV infection resulted in altered protein expression of lipid metabolism in hepatocytes. Knocking down the transcription factor PPAR-γ in hepatocytes effectively inhibited CMV infection. Discussion Our findings underscore the immune system's response to early-stage MCMV infection and the subsequent impact on hepatic lipid metabolism in infant mice. This research provides new insights into the mechanisms of CMV infection and could pave the way for novel therapeutic strategies.